Performance analysis of channel model simplifications for MIMO OTA LTE UE testing - Landmann, Markus; Grossmann, Marcus; Phatak, Naveen; Schneider, Christian; Thomae, Reiner; Del Galdo, Giovanni (2013 7th European Conference on Antennas and Propagation, EuCAP 2013, 2013)
In the context of MIMO OTA testing, the impact of channel model simplifications on the performance of a 2×2 MIMO LTE system in the closed-loop spatial multiplexing transmission mode is analyzed. Specifically, a measurement based channel model is applied which allows the embedding of application antennas such as the proposed CTIA reference antennas. Three different channel models (a 3-D full, a 2-D full and a 2-D single polarimetric model) are considered. Numerical results on system capacity and throughput simulations are illustrated by several examples. It is found that the relative error in terms of capacity between the 3-D full and the 2-D full polarimetric model is less than 10% for uplink transmissions when the signal-to-noise ratio target is reached with the available transmit power. Further, the results show that when completely neglecting the polarization characteristics of the propagation environment, the throughput and capacity errors can rise up to 50%. In addition, simulation results indicate that the LTE system with CTIA 'Nominal' reference antennas outperforms the LTE system with 'Good' reference antennas for the uplink transmission in some channel fading environments. © 2013 EurAAP.
CRIS-Team Scopus Importer:2025-11-10
Keywords: channel model simplifications; CTIA reference antennas; LTE throughput; MIMO OTA